Growth kinetic and characterization of RF-Sputtered ZnO:Al Nanostructures - Supab Choopun (2018)
ZnO:Al nanostructures with 1% by mole of Al were prepared by radio frequency sputtering on copper and quartz substrates. The ZnO:Al nanostructures obtained exhibited needle- or tree-like structures with the diameter ranging from 30 to 100 nm. It was suggested that these ZnO:Al nanostructures could be single-crystalline hexagonal structures growing along the direction with branching along the 〈0001〉 direction. From Hall measurement, ZnO:Al nanostructures had a resistivity in the order of 10-2 Ω·cm, a carrier concentration of 1020 cm-3, and a Hall mobility of 3 cm2·(V·s)-1. From X-ray diffraction, transmission electron microscopy and Raman results, ZnO:Al nanostructures had direction perpendicular to the surface, whereas ZnO nanobelts had the c-axis perpendicular to the surface. In addition, the growth mechanism of the wire and belt-like nanostructure could be explained by kinetics of anisotropic growth via a vapor-solid mechanism. This information would be useful for further applications of ZnO:Al nanostructures. © 2007 The American Ceramic Society.